2016
DOI: 10.1007/s11325-016-1316-1
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparity in adherence to positive airway pressure among US veterans

Abstract: CPAP compliance is considerably lower in AAs than in Whites, though severity of OSA modifies this association. These findings are not readily explained by differences in demographics or comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…20,21,22 Several studies including the current analysis have observed that adherence with PAP is lower among AA patients. 6,23 Lower socioeconomic status and its association with poorer understanding of the risks and consequences of SDB is an important explanation. 7,24 However, cultural differences as well as shorter sleep durations and more insomnia symptoms among AA are likely contributing factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21,22 Several studies including the current analysis have observed that adherence with PAP is lower among AA patients. 6,23 Lower socioeconomic status and its association with poorer understanding of the risks and consequences of SDB is an important explanation. 7,24 However, cultural differences as well as shorter sleep durations and more insomnia symptoms among AA are likely contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 African Americans (AA) also tend to be more obese, have higher rates of hypertension and significantly greater oxygen desaturation during SDB events on polysomnography (PSG); 5 they have been shown to be less adherent to continuous positive airway pressure (CPAP) therapy for SDB. 6 Factors responsible for this disparity in CPAP compliance are unclear, but may partially be explained by lower socioeconomic status 7 and shorter sleep durations. 8 The impact of this sub-optimal CPAP adherence on health outcomes in African Americans is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…While older age was associated with greater mean daily PAP use among whites, younger age was associated with greater daily PAP use among blacks. In the largest retrospective study examining race-ethnicity and PAP adherence to date [42], Schwartz et al (n=2,172; 233 blacks) found that black veterans were about half as likely as white veterans to use PAP ≥ 4 hrs daily on 70% of day during the initial two weeks (RR 0.58 95% CI: 0.43–0.77) and after six months of therapy (RR 0.52 95% CI 0.36–0.74). These findings were independent of several covariates including age, gender, BMI, OSA severity, oxygen nadir, sleepiness, marital status, and median neighborhood income.…”
Section: Resultsmentioning
confidence: 99%
“…Although we compared the MCI +CPAP and the MCI −CPAP groups on 22 potential baseline confounders, and controlled for the differences in our analysis, the groups may have been different on unidentified variables that may have affected the study outcomes. Like others, we found that whites were more likely to adhere to CPAP, and we controlled for race in the data analysis. We also controlled for marital status.…”
Section: Discussionmentioning
confidence: 99%